OPTIMALISASI PENJUALAN PARFUM MENGGUNAKAN DIRECT MARKETING AND FULFILLMENT DENGAN PENDEKATAN CRM - Yolanda Y.P Rumapea; Olivia Harefa; Asaziduhu Gea (METHODIKA: Jurnal Teknik Informatika dan Sistem Informasi, 2021)
Currently, Customer Relationship Management is very important to foster relationships between customers and sellers and provide information carried out by customers. Kzu Parfum shop is one of the SMEs (Micro, Small, and Medium Enterprises) which is engaged in selling perfume and perfume seeds. The problems faced by the Kzu Parfum Store at this time are that there is no system that can run in managing sales records, there are no special media to promote its products, and orders are still done manually by visiting the store to buy the perfume. In this study, the authors implement CRM with the Direct Marketing and Fulfillment method as a medium of information at the Kzu Parfum store, which aims to make it easier for Kzu Parfum to convey information to consumers. The sales system application is expected to solve the problems of the Kzu Parfum Shop, where transactions usually use an online mechanism and provide facilities such as products that contain images and product information. In the catalog, consumers can find information about the product ordering process and can generate sales transaction reports.